In vivo NAD(P)H fluorescence from the epidermal cells of onion (Allium сера) bulb scale leaves - Slezák Csilla; Herrhofer Éva; Laskay Gábor (2010)
In vivo fluorescence measurements were carried out on intact layers of onion (Allium cepa) bulb scale leaf epidermal cells in order to study if the blue autofluorescence can be used for monitoring the redox satate of NAD(P)H in these plant leaf cells and/or mitochondria in vivo. When recording the fluorescence spectra (excited at 340 nm) of the intact cell layers, a well-resolvable shoulder was always present at around 465-469 nm. An empirical formula ((F467-F500)/F500) was derived to normalize the differential fluorescence intensity of the shoulder at 467 nm (F467-F500) to that at 500 nm (F500). Treatment of the cell layers with 1 mM KCN, an inhibitor of the mitochondrial electron transport chain at Complex IV led to an increase in the (F467-F500)/F500 fluorescence emission ratio, leaving the fluorescence intensity of the untreated cell layers unchanged. Qualitatively similar results were obtained using 1 mM rotenone, an inhibitor of Complex I (NADH-oxidase) of the mitochondrial electron transport chain. These findings imply that the fluorescence at 467 nm derives dominantly from mitochondrial NADH in the epidermal cells of onion scale leaves. Moreover, it is concluded that the (F467-F500)/F500 fluorescence emission ratio can be used to observe changes in the redox state of the NAD pool in these cells.